2009
DOI: 10.1007/s12119-009-9054-1
|View full text |Cite
|
Sign up to set email alerts
|

Violence, Cultural Display and the Suspension of Sexual Prejudice

Abstract: Prejudice and violence directed against gay men, lesbians and other sexual groups have been viewed as ubiquitous and relatively fixed phenomena in contemporary societies. This perspective must be reconciled with the increased depiction of marginal sexualities and commercial 'queering' of mainstream media and popular culture. This paper presents and discusses data from two sources. Firstly, interviews conducted with self-identifying heterosexuals at the annual Sydney Gay and Lesbian Mardi Gras (SGLMG) parade su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Confirming past research ( Cortina et al, 2001 , 2002 , 2013 ; Settles and O’Connor, 2014 ), our findings suggest that women are especially vulnerable to being treated uncivilly at work. However, refuting past research ( Tomsen and Markwell, 2009 ; Woodford et al, 2012 ), sexual minorities (in general) did not differ from heterosexuals in the extent to which they experienced incivility.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Confirming past research ( Cortina et al, 2001 , 2002 , 2013 ; Settles and O’Connor, 2014 ), our findings suggest that women are especially vulnerable to being treated uncivilly at work. However, refuting past research ( Tomsen and Markwell, 2009 ; Woodford et al, 2012 ), sexual minorities (in general) did not differ from heterosexuals in the extent to which they experienced incivility.…”
Section: Discussioncontrasting
confidence: 53%
“…Research in other areas (e.g., education, cultural studies) suggests that sexual minorities may be at risk for experiencing subtle maltreatment. For example, Woodford et al (2012) found that sexual minority college students were more likely to experience incivility at school compared to their heterosexual counterparts and Tomsen and Markwell (2009) found that sexual minorities reported experiences of threat and incivility during, and especially after, LGBT-based public events. In the microaggressions (i.e., discrimination in the form of verbal, behavioral, and environmental slights and indignities toward oppressed groups; Sue, 2010 ) literature, a number of qualitative (e.g., focus group) studies have documented sexual minorities’ experiences of subtle discrimination in the context of the university ( Nadal et al, 2011 ; Platt and Lenzen, 2013 ), community ( Nadal et al, 2011 ; Sarno and Wright, 2013 ; Bostwick and Hequembourg, 2014 ), and psychotherapy ( Shelton and Delgado-Romero, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual prejudice can be elusive and respond to a number of purposes. Sexual prejudice can be concealed or suspended temporarily in exchange for titillation, such as that among non-LGBTI onlookers at Pride parades (Tomsen & Markwell, 2009). It can include seemingly positive components, such as paternalistic views, besides the negative ones (Dixon et al, 2013).…”
mentioning
confidence: 99%